The PENGARUH MEKANISME KOMITE AUDIT TERHADAP INCOME SMOOTHING - Adisti Maharani Krisna (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to determine how the influence of the audit committee mechanism on income smoothing, where the audit committee mechanism is divided into four, namely the size of the audit committee, the independence of the audit committee, the expertise of the audit committee, and the number of audit committee meetings. Later this research is expected to provide input to companies to publish quality financial reports. The sample of this study uses LQ45 companies with a total of 114 observed companies. The results showed that the size and independence of the audit committee had a negative effect on income smoothing, while the expertise and number of audit committee meetings had not had a significant effect.